Students' Experiences With AI-Assisted Online Assessment In English Writing Courses: A Case Study - Taufiqul Hakim Waliyuddin Fathurrohman Al Furqon; Nur Aisyah Zulkifli (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2026)
The integration of artificial intelligence (AI) tools in academic settings has fundamentally transformed how students engage with writing tasks and assessment processes. This qualitative case study explores the experiences of students with AI-assisted online assessment in English writing courses. Data were collected from 5 undergraduate students in an English Language Education program through semi-structured interviews and document analysis. Employing Braun and Clarke's (2006) thematic analysis, four major themes emerged: (1) AI enhances writing confidence, (2) AI facilitates immediate feedback, (3) AI supports self-assessment, and (4) ethical concerns and dependency. The findings reveal that AI-assisted online assessment provides meaningful learning support, yet raises significant concerns related to academic integrity and over-reliance on technology. Implications for instructors, students, and institutions are discussed, along with recommendations for future research.